2013
DOI: 10.1002/bio.2600
|View full text |Cite
|
Sign up to set email alerts
|

Size‐dependent temperature sensitivity of photoluminescence peak position of CdTe quantum dots

Abstract: The size dependence of the temperature coefficient (sensitivity) of the photoluminescence (PL) peak position of CdTe quantum dots stabilized by thioglycolic acid in aqueous solution has been investigated. Temperature sensitivity increases as the average radius of CdTe quantum dots decreases. This must be taken into account in the design of solar light concentrators and light-emmiting diode-monitors as well as other technologies in which a fine tuning of the light emission is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…We noticed that similar to optical bandgap (Eg opt ), electrochemical (Eg CV ) bandgap of QDs demonstrates the same trend, so the temperature sensitivity of QDs of a certain size can be determined from the slope of the linear regression approximation plotted in the coordinates Eg vs. αT 2 / (T + θ). In this case, the temperature coefficient α will describe the change in the PL energy when the temperature is changed by 1 K, and E 0 is the PL energy at 0 K [23].…”
Section: Temperature-dependent Bandgap Variation In Cdte/cds Qdsmentioning
confidence: 99%
“…We noticed that similar to optical bandgap (Eg opt ), electrochemical (Eg CV ) bandgap of QDs demonstrates the same trend, so the temperature sensitivity of QDs of a certain size can be determined from the slope of the linear regression approximation plotted in the coordinates Eg vs. αT 2 / (T + θ). In this case, the temperature coefficient α will describe the change in the PL energy when the temperature is changed by 1 K, and E 0 is the PL energy at 0 K [23].…”
Section: Temperature-dependent Bandgap Variation In Cdte/cds Qdsmentioning
confidence: 99%
“…There are only few publications that investigate the temperature dependence of the band gap energy on nanoparticles. 49 The effects that can influence the band gap shift and the line broadening under discussion are, for example, the strain in the crystal lattice, the termination of the dangling bonds at the nanoparticle surface, the temperature of the nanoparticle, and the change of the effective electron/hole mass due to changes in the band structure.…”
Section: Resultsmentioning
confidence: 99%
“…The fitted α values were in the range of (2.9–3.4) × 10 −4 eV/K, which is very close to the value of bulk CdTe (0.3 × 10 −4 eV/K) [ 33 ]. The β values changed from 312 to 146 K for CdTe NC/PVA films with larger sizes, which were similar to that of bulk CdTe (160 K) [ 34 ], due to lattice softening from bulk to NCs [ 35 ]. The fitting results showed that the tendency of the temperature-dependent bandgap was consist with traditional II-VI NCs.…”
Section: Resultsmentioning
confidence: 99%